In-situ crystallization type catalytic cracking heavy metal pollution element collector and preparation method thereof

By using the in situ crystallization catalytic catalytic catalytic cracking heavy metal pollution element capture agent in catalytic cracking catalysts, it is difficult to improve the problem of catalyst anti -V, Ni and Fe pollution properties at the same time. Significantly improved.

CN116832844BActive Publication Date: 2025-01-28SHANXI KAITE TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310313633.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-01-28
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the anti-V, Ni and Fe pollution properties of catalytic cracking catalysts at the same time, especially when multiple heavy metal pollution elements are present in the raw oil at the same time.

Method used

The in -situ crystallization catalytic cracking heavy metal pollution element capture agent. The catcher is a mixed substrate from aluminum clay and magnesium clay. The compound structure unit significantly improves the anti -heavy metal pollution performance of the catalyst.

Benefits of technology

The catcher can significantly improve the overall anti -V, Ni and Fe pollution performance of catalytic cracking catalysts, improve the ability to transform heavy oil conversion and selectivity of cracking products, and have good practical application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides an in-situ crystallization type catalytic cracking heavy metal pollution element scavenger and a preparation method thereof. The preparation method comprises the following steps: (1) at room temperature, aluminous clay, magnesia clay, an activation component, aluminum sol and deionized water are fully mixed and slurried, and then spray-dried to obtain clay microspheres; (2) the clay microspheres obtained in (1) are roasted at a temperature of 500°C to 800°C for 1 to 4 hours to obtain activated clay microspheres; (3) the activated clay microspheres obtained in (2), carbonate and deionized water are mixed, the pH value of the system is adjusted to 10 to 13 with a saturated alkaline solution, and then the mixture is transferred to an autoclave and allowed to stand for crystallization at a temperature of 80°C to 120°C for 6 to 24 hours, and the in-situ crystallization type catalytic cracking heavy metal pollution element scavenger is obtained after filtering, washing and drying. The present invention can comprehensively and significantly improve the anti-V, Ni and Fe pollution performance of the catalytic cracking catalyst by a simple compounding method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalytic cracking heavy metal pollution element scavenger and a preparation method thereof, and in particular to an in-situ crystallization type catalytic cracking heavy metal element scavenger capable of comprehensively improving the V, Ni and Fe pollution resistance of catalytic cracking catalysts and a preparation method thereof. Background Art

[0002] Catalytic cracking (FCC) is an important secondary processing technology in the oil refining industry, and plays a pivotal role in the oil refining industry. As the world's crude oil becomes increasingly heavy and inferior, heavy oil catalytic cracking has developed rapidly and has accounted for 25% of the world's total crude oil processing capacity. However, in addition to a large amount of colloids and asphaltene, heavy oil also contains a large amount of heavy metal components, so the requirements for the anti-heavy metal pollution performance of catalytic cracking catalysts are getting higher and higher.

[0003] Currently, for catalytic cracking catalysts, V, Ni and Fe in the crude oil are the three main heavy metal pollution elements, and their pollution mechanisms for catalytic cracking catalysts are different. Among them, V element can form vanadic acid (H3VO4) in the high-temperature hydrothermal regeneration environment of FCC catalyst. Since the formed vanadic acid is highly acidic, it is very easy to destroy the skeleton structure of the zeolite molecular sieve, the active component of the catalytic cracking catalyst, thereby causing the catalyst activity to decrease and the heavy oil conversion capacity to decrease significantly; Ni element will be deposited on the catalyst surface in the form of NiO during the high-temperature regeneration process of the catalytic cracking catalyst. In the catalytic cracking hydrogen reaction environment, the deposited NiO will be reduced to form zero-valent nickel (Ni 0 ) species. 0 The species has a strong dehydrogenation activity, which will significantly increase the dehydrogenation reaction of oil and gas molecules and generate a large amount of hydrogen, which will lead to an increase in the dry gas yield of the catalytic cracking unit, causing the compressor of the unit to run at high load, which will seriously affect the stable operation of the unit. During the high-temperature hydrothermal regeneration of the catalytic cracking catalyst, the Fe element will form a low-melting point eutectic with Na2O and SiO2 present in the catalyst. Since the formed low-melting point eutectic has strong fluidity, it is very easy to block the catalyst pore structure, seriously affecting the diffusion and mass transfer of oil and gas molecules in the catalyst pores, resulting in a decrease in the yield of light oil products and an increase in the coke yield. Research on improving the resistance of catalytic cracking catalysts to heavy metal pollution has always been a hot topic of concern. In summary, there are roughly three ways:

[0004] (1) Use liquid FCC heavy metal pollution element passivator. For example, CN1068588 discloses a heavy metal liquid passivator for improving the heavy metal pollution resistance of FCC catalysts. The liquid passivator is composed of three parts: antimony and / or bismuth carboxyl compounds, reaction medium and solubilizer. CN1294173 discloses a water-soluble heavy metal passivator, which is mainly composed of antimony, aluminum and rare earth lanthanum, which can significantly reduce the poisoning and deactivation of FCC catalysts and improve the yield of light oil products such as gasoline. JP01284580 discloses a solution prepared with antimony salts. After using this solution, the generation of hydrogen and coke can be significantly reduced.

[0005] (2) Directly adding a modifying element component with heavy metal pollution element passivation performance to the FCC catalyst, usually rare earth lanthanum and cerium. For example, patents such as CN85106050A, US4921824, EP347248, and JP0712661 introduce lanthanide modifying elements into the catalyst to improve the catalyst's resistance to vanadium pollution.

[0006] (3) Use special FCC catalyst matrix materials. Currently, the most commonly used are various types of macroporous and mesoporous alumina materials (Petroleum Refining and Chemical Industry, 2019, 07: 80-84; Petroleum Refining and Chemical Industry, 2017, 05: 52-55; Industrial Catalysis, 2002, 02: 50-53.).

[0007] However, each of the above three methods has some obvious defects. Liquid heavy metal passivators are not only expensive, but also highly toxic, and are rarely used on the market. The use of rare earth modified elements or special catalyst matrix materials will not only significantly increase the production cost of the catalyst, but also are often only effective for a single heavy metal pollution element, and cannot comprehensively improve the catalyst's resistance to V, Ni and Fe pollution. However, V, Ni and Fe and other heavy metal pollution elements often exist in crude oil at the same time. Therefore, there is an urgent need for a technology that can comprehensively improve the resistance of catalytic cracking catalysts to V, Ni and Fe. Summary of the invention

[0008] In view of the above problems, the object of the present invention is to provide an in-situ crystallized catalytic cracking heavy metal pollution element collector and a preparation method thereof, which can simultaneously and significantly improve the catalytic cracking catalyst's resistance to V, Ni and Fe pollution.

[0009] The present invention discloses an in-situ crystallization type catalytic cracking heavy metal pollution element collector and a preparation method thereof, wherein the preparation method comprises the following steps:

[0010] (1) at room temperature, aluminous clay, magnesia clay, an activating component, aluminum sol and deionized water are fully mixed and slurried, and then spray-dried to obtain clay microspheres;

[0011] (2) calcining the clay microspheres obtained in (1) at a temperature of 500° C. to 800° C. for 1 to 4 hours to obtain activated clay microspheres;

[0012] (3) The activated clay microspheres obtained in (2), carbonate and deionized water are mixed, and the pH value of the system is adjusted to 10-13 with a saturated alkaline solution, and then transferred to an autoclave and allowed to stand for crystallization at a temperature of 80° C. to 120° C. for 6-24 hours. After filtering, washing and drying, the in-situ crystallization type catalytic cracking heavy metal pollution element collector is obtained.

[0013] In the preparation method provided by the present invention, the aluminous clay in step (1) can be one or more of kaolin, halloysite, rectorite, boehmite and bentonite aluminum-containing clay minerals, preferably kaolin.

[0014] In the preparation method provided by the present invention, the magnesia clay in step (1) can be one or more of attapulgite, magnesium-rich montmorillonite, sepiolite, illite and chlorite magnesium-containing clay minerals, preferably attapulgite.

[0015] In the preparation method provided by the present invention, the activating component in step (1) can be one or more of sodium borate, sodium metaborate, ammonium borate, ammonium metaborate, boric oxide and boric acid, preferably boric oxide.

[0016] In the preparation method provided by the present invention, the mass ratio of aluminous clay: magnesia clay: activating component: aluminum sol (calculated by Al2O3 mass): deionized water in step (1) is 1: 0.5-10: 0.001-0.1: 0.05-0.5: 5-50, preferably 1: 1-5: 0.01-0.05: 0.1-0.3: 5-20.

[0017] In the preparation method provided by the present invention, the carbonate in step (3) can be one or more of sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, ammonium carbonate and ammonium bicarbonate, preferably sodium carbonate.

[0018] In the preparation method provided by the present invention, the saturated alkaline solution in step (3) can be one or more of a saturated sodium hydroxide solution, a saturated potassium hydroxide solution and a saturated ammonia solution, preferably a saturated sodium hydroxide solution.

[0019] In the preparation method provided by the present invention, the mass ratio of the activated clay microspheres: carbonate: deionized water in step (3) is 1: 0.001-0.1: 1-20, preferably 1: 0.01-0.05: 4-10.

[0020] In the preparation method provided by the present invention, the spray drying molding in step (1) is a general technical process in the art.

[0021] An in-situ crystallization type catalytic cracking heavy metal pollution element collector is prepared according to the above preparation method.

[0022] The in-situ crystallization type catalytic cracking heavy metal pollution element collector provided by the present invention uses aluminum clay and magnesium clay as a mixed matrix, first activates the magnesium and aluminum elements in the clay structure by roasting combined with adding an activation component, and then constructs the magnesium aluminum dihydroxy compound structural unit with excellent heavy metal element pollution resistance performance in situ on the matrix surface in a highly dispersed state by in-situ crystallization, thereby obtaining an in-situ crystallization type catalytic cracking heavy metal pollution element collector. Through a simple compounding method, the in-situ crystallization type catalytic cracking heavy metal pollution element collector can comprehensively and significantly improve the V, Ni and Fe pollution resistance of the catalytic cracking catalyst, and has good practical application prospects. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0024] Raw material sources and main indicators:

[0025] Kaolin, attapulgite, alumina sol (Al2O3 content: 18%) and catalytic cracking catalyst were purchased from a domestic catalyst manufacturer and are qualified industrial products; boron oxide (B2O3), sodium hydroxide (NaOH) and sodium carbonate (Na2CO3) are all commercially available analytical grade reagents.

[0026] Analysis and evaluation:

[0027] A catalytic cracking catalyst was compounded with a 6 wt% collector, and then sodium metavanadate (NaVO3), nickel nitrate (Ni(NO3)2·6H2O) and ferric nitrate (Fe(NO3)3·9H2O) were used as metal element pollution sources, and the composite catalyst was contaminated with V, Ni and Fe (V: 4000ppm; Ni: 7000ppm; Fe: 8000ppm) by an equal volume impregnation method. After the contaminated composite catalyst was aged at 800°C and 100% water vapor, the anti-V, Ni and Fe pollution performance of the composite catalyst contaminated sample was evaluated on an ACE (Advanced cracking evaluation, Kayser R+MultiMode microreactor) device. The reaction temperature was 530°C, the catalyst-to-oil ratio was 5, and the properties of the raw oil were shown in Table 1.

[0028] Table 1 Raw oil properties

[0029]

[0030]

[0031] Example 1

[0032] The present invention provides a method for preparing an in-situ crystallization type catalytic cracking heavy metal pollution element collector, the steps of which are as follows:

[0033] (1) At room temperature, 100 g of kaolin, 100 g of attapulgite, 1 g of boron oxide, 56 g of aluminum sol solution and 500 g of deionized water were fully mixed and slurried, and then spray-dried to obtain clay microspheres.

[0034] (2) The clay microspheres obtained in (1) were calcined at 800°C for 1 hour to obtain activated clay microspheres.

[0035] (3) 100 g of the activated clay microspheres obtained in (2), 1 g of sodium carbonate and 1000 g of deionized water were mixed, and the pH of the system was adjusted to 13 with a saturated sodium hydroxide solution. The mixture was then transferred to an autoclave and allowed to stand for crystallization at 80° C. for 24 hours. After filtering, washing and drying, the in-situ crystallization catalytic cracking heavy metal pollution element collector C1 was obtained.

[0036] Example 2

[0037] The present invention provides a method for preparing an in-situ crystallization type catalytic cracking heavy metal pollution element collector, the steps of which are as follows:

[0038] (1) At room temperature, 200 g of kaolin, 600 g of attapulgite, 6 g of boron oxide, 222 g of aluminum sol solution and 2000 g of deionized water were fully mixed and slurried, and then spray-dried to obtain clay microspheres.

[0039] (2) The clay microspheres obtained in (1) were calcined at 700°C for 2 hours to obtain activated clay microspheres.

[0040] (3) 300 g of the activated clay microspheres obtained in (2), 9 g of sodium carbonate and 2100 g of deionized water were mixed, and the pH value of the system was adjusted to 11 with a saturated sodium hydroxide solution. The mixture was then transferred to an autoclave and allowed to stand for crystallization at 100° C. for 12 hours. After filtering, washing and drying, the in-situ crystallization catalytic cracking heavy metal pollution element collector C2 was obtained.

[0041] Example 3

[0042] The present invention provides a method for preparing an in-situ crystallization type catalytic cracking heavy metal pollution element collector, the steps of which are as follows:

[0043] (1) At room temperature, 300 g of kaolin, 1500 g of attapulgite, 15 g of boron oxide, 500 g of aluminum sol solution and 6000 g of deionized water were fully mixed and slurried, and then spray-dried to obtain clay microspheres.

[0044] (2) The clay microspheres obtained in (1) were calcined at 550°C for 4 hours to obtain activated clay microspheres.

[0045] (3) 500 g of the activated clay microspheres obtained in (2), 25 g of sodium carbonate and 2500 g of deionized water were mixed, and the pH value of the system was adjusted to 10 with a saturated sodium hydroxide solution. The mixture was then transferred to an autoclave and allowed to stand for crystallization at 120° C. for 6 hours. After filtering, washing and drying, the in-situ crystallization catalytic cracking heavy metal pollution element collector C3 was obtained.

[0046] Table 2 Heavy oil catalytic cracking reaction performance of vanadium contaminated catalyst

[0047] Yield, % Catalytic cracking catalyst Catalytic cracking catalyst compound C1 Dry gas 2.94 3.17 Liquefied gas 19.66 20.14 gasoline 48.90 51.93 diesel fuel 13.44 10.23 heavy oil 6.00 4.27 Coke 9.06 10.26 Total liquid yield 82.00 82.30

[0048] It can be seen from the results in Table 2 that after the same amount of V pollution, compared with the simple catalytic cracking catalyst, after compounding the collector C1 provided by the present invention, the heavy oil yield of the composite catalyst decreased significantly, showing a stronger heavy oil conversion ability, while the selectivity of the cracking product was also greatly improved, and the gasoline and overall liquid yields increased significantly. The above results show that compounding an in-situ crystallization type catalytic cracking heavy metal pollution element collector provided by the present invention can significantly improve the overall V pollution resistance of the catalytic cracking catalyst.

[0049] Table 3 Heavy oil catalytic cracking performance of Ni-contaminated catalysts

[0050]

[0051]

[0052] It can be seen from the results in Table 3 that after the same amount of Ni pollution, compared with the pure catalytic cracking catalyst, after compounding the collector C2 provided by the present invention, the dry gas and coke yields of the composite catalyst are significantly reduced, while the gasoline and total liquid yields are significantly improved. The above results show that compounding an in-situ crystallization type catalytic cracking heavy metal pollution element collector provided by the present invention can significantly improve the overall anti-Ni pollution performance of the catalytic cracking catalyst.

[0053] Table 4 Heavy oil catalytic cracking performance of Fe-contaminated catalysts

[0054] Yield, % Catalytic cracking catalyst Catalytic cracking catalyst compound C3 Dry gas 2.65 2.77 Liquefied gas 22.99 22.22 gasoline 48.55 51.93 diesel fuel 11.18 10.69 heavy oil 8.06 4.94 Coke 6.57 7.45 Total liquid yield 82.72 84.84

[0055] It can be seen from the results in Table 4 that after the same amount of Fe pollution, compared with the simple catalytic cracking catalyst, after compounding the collector C3 provided by the present invention, the heavy oil yield of the composite catalyst is greatly reduced, while the gasoline and total liquid yields are significantly increased. The above results show that compounding an in-situ crystallization type catalytic cracking heavy metal pollution element collector provided by the present invention can significantly improve the overall anti-Fe pollution performance of the catalytic cracking catalyst.

[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an in-situ crystallization type catalytic cracking heavy metal pollution element collector, the preparation method comprising the following steps: (1) at room temperature, aluminous clay, magnesia clay, activation component, aluminum sol and deionized water are fully mixed and slurried, the mass ratio of aluminous clay:magnesia clay:activation component:aluminum sol based on Al2O3 mass:deionized water is 1:0.5-10:0.001-0.1:0.05-0.5:5-50, and then spray-dried to obtain clay microspheres; (2) calcining the clay microspheres obtained in (1) at a temperature of 500° C. to 800° C. for 1 to 4 hours to obtain activated clay microspheres; (3) mixing the activated clay microspheres obtained in (2), carbonate and deionized water, with a mass ratio of clay microspheres: carbonate: deionized water = 1: 0.001-0.1: 1-20, adjusting the system pH to 10-13 with a saturated alkaline solution, and then transferring to an autoclave and standing at 80° C. to 120° C. for crystallization for 6-24 hours, filtering, washing and drying to obtain the in-situ crystallization type catalytic cracking heavy metal pollution element capture agent; in, The activating component in step (1) is one or more of sodium borate, sodium metaborate, ammonium borate, ammonium metaborate, boric oxide and boric acid; the carbonate in step (3) is one or more of sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, ammonium carbonate and ammonium bicarbonate.

2. The preparation method according to claim 1, characterized in that: The aluminous clay in step (1) is one or more of kaolin, halloysite, rectorite, boehmite and bentonite aluminum-containing clay minerals.

3. The preparation method according to claim 1, characterized in that: The magnesia clay in step (1) is one or more of attapulgite, magnesium-rich montmorillonite, sepiolite, illite and chlorite magnesium-containing clay minerals.

4. The preparation method according to claim 1, characterized in that: The mass ratio of aluminous clay: magnesia clay: activating component: aluminum sol in terms of Al2O3 mass: deionized water in step (1) is 1:1-5:0.01-0.05:0.1-0.3:5-20.

5. The preparation method according to claim 1, characterized in that: The saturated alkaline solution in step (3) is one or more of a saturated sodium hydroxide solution, a saturated potassium hydroxide solution and a saturated ammonia solution.

6. The preparation method according to claim 1, characterized in that: The mass ratio of clay microspheres: carbonate: deionized water in step (3) is 1: 0.01-0.05: 4-10.

7. An in-situ crystallization type catalytic cracking heavy metal pollution element collector, characterized in that: The method is prepared according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Improved catalytic cracking process

    CN85106050A

  • Cracking of hydrocarbons

    EP0347248A1

  • Passivating agent in catalytic cracking of hydrocarbon

    JP1989284580A

  • Method for measuring pressure of gas containing oxygen on surface, method for visualizing gas containing oxygen on surface and pressure sensitive composition

    JP1995012661A

  • Metal passivating catalyst composition for cracking hydrocarbons

    US4921824A